1997
DOI: 10.1107/s0907444997000838
|View full text |Cite
|
Sign up to set email alerts
|

Structure of apo duck ovotransferrin: the structures of the N and C lobes are in the open form

Abstract: The structure of apo duck ovotransfemn (APODOT) has been determined at a resolution of 4.0A by the molecular replacement method using the structure of duck ovotransfemn (DOT) as the search model. The DOT structure contains two iron binding sites; one in the N-terminal lobe lying between domains N1 and N2 and one in the C-terminal lobe between domains C 1 and C2. Both lobes have a closed structure. Models of various forms of both the N and C lobes were used in the search. The final model was refined to give an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…2). The extent and mode of the opening were almost the same as in the N-lobes of the whole molecules of lactoferrin (11) and duck (12) and hen 3 ovotransferrin: as calculated by the rigid body motion method (27), the domains move 49.7°around a rotation axis passing through the Fig. 3a is a stereo and Tyr 191 ligands.…”
Section: Quality Of the Final Model-mentioning
confidence: 57%
See 1 more Smart Citation
“…2). The extent and mode of the opening were almost the same as in the N-lobes of the whole molecules of lactoferrin (11) and duck (12) and hen 3 ovotransferrin: as calculated by the rigid body motion method (27), the domains move 49.7°around a rotation axis passing through the Fig. 3a is a stereo and Tyr 191 ligands.…”
Section: Quality Of the Final Model-mentioning
confidence: 57%
“…Four of the six Fe 3ϩ coordination sites are occupied by the protein ligands of two tyrosine residues, one aspartic acid residue, and one histidine residue (Asp 60 , Tyr 92 , Tyr 191 , and His 250 in ovotransferrin N-lobe) and the other two, by a synergistic anion, physiologically bidentate CO 3 2Ϫ (2-10). For the iron-free apo form, however, x-ray crystallographic (11)(12)(13) and solution scattering (14 -17) analyses have revealed that all of the transferrin lobes, except for the lactoferrin C-lobe in crystal, assume a conformation with an opening of the interdomain cleft. This implies that transferrin initially binds the Fe 3ϩ ion in the open form before being transformed into the closed holo form (18,19 A major difficulty encountered in the structural analysis for the intermediate is to prepare a stable protein form that reasonably mimics it.…”
mentioning
confidence: 99%
“…The structure of MALT, with both the N and the C lobes closed, is very different from that of HALT, which has the N lobe open and the C lobe closed (Norris et al, 1991), and that of DAOT (Rawas et al, 1997), which has both lobes open. An examination of the interdomain interactions in the N lobes of MDLT and HDLT clearly indicates the presence of stronger attractive interactions in the former.…”
Section: Figurementioning
confidence: 98%
“…In the presence of iron, interdomain interactions result in the closed forms of these proteins. However, the crystal structures of duck apoovotransferrin (DAOT; Rawas et al, 1997) and human apolactoferrin (HALT; Norris et al, 1991) showed different domain association behaviours. In the former, both lobes adopt open conformations, while in the latter the N lobe has an open structure whereas the C lobe prefers a closed conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the six coordination sites of Fe 3ϩ , four are occupied by protein ligands (two Tyr, one Asp, and one His residues), and the other two are occupied by a bidentate carbonate anion. In the Fe 3ϩ -free apo form, both the lobes of ovotransferrin and serum transferrin assume a conformation with an opening of the interdomain cleft, as revealed by x-ray crystallographic (25)(26)(27) and solution scattering (28 -31) analyses. The anioninduced Fe 3ϩ release by transferrins, therefore, should be closely related to the opening of the domains in either lobe.…”
mentioning
confidence: 99%